2014
DOI: 10.7162/s1809-97772013000200010
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss in the elderly: History of occupational noise exposure

Abstract: Summary Introduction: Noise exposure is one of the most common health risk factors, and workers are exposed to sound pressure levels capable of producing hearing loss. Aim: To assess the prevalence of hearing loss in the elderly and its possible association with a history of occupational noise exposure and with sex. Methods: A prospective study in subjects aged over 60 years. The subjects underwent anamnesis and audiological assessment. The Mann–Whitney test and multiple logistic regression, with 95% confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…The mean age for the first test was higher in the NEG (43.3 years) as opposed to the NNEG (36.6 years), which may act as a moderating factor in the sense that the older the participant, because of the effect of ageing on the ear, the higher their initial hearing thresholds will be. This finding can also be compared to findings that suggest pathological changes from early noise exposure to substantially increase the risk of inner ear ageing and related hearing loss in later years (Campo et al, 2011;Gates et al, 2000;Kujawa & Liberman, 2006;Meneses-Barriviera, Melo, De Moraes, & Marchiori, 2013). Although we cannot accurately identify the specific mechanism for the accelerated increase in hearing thresholds seen in this analysis, it seems possible that the noise-damaged ear does not age at the same rate as an ear without known noise damage; this again points to a possible super additive interaction between NIHL and ARHL.…”
Section: Discussionmentioning
confidence: 90%
“…The mean age for the first test was higher in the NEG (43.3 years) as opposed to the NNEG (36.6 years), which may act as a moderating factor in the sense that the older the participant, because of the effect of ageing on the ear, the higher their initial hearing thresholds will be. This finding can also be compared to findings that suggest pathological changes from early noise exposure to substantially increase the risk of inner ear ageing and related hearing loss in later years (Campo et al, 2011;Gates et al, 2000;Kujawa & Liberman, 2006;Meneses-Barriviera, Melo, De Moraes, & Marchiori, 2013). Although we cannot accurately identify the specific mechanism for the accelerated increase in hearing thresholds seen in this analysis, it seems possible that the noise-damaged ear does not age at the same rate as an ear without known noise damage; this again points to a possible super additive interaction between NIHL and ARHL.…”
Section: Discussionmentioning
confidence: 90%
“…Regarding self-reported hearing impairment grades by HHIE-S, the present study indicated that the majority(85.2%) of elderly had significant hearing impairment (severe and profound) this result supported by Mattosand Veras(2010) (44) who carried out a study in Brazil and found that significant hearing loss was found in 82.4%. Moreover in study conducted by Barriviera et al (2013) (45) in Northern Parana; their finding indicated that 91.56% of subjects had significant hearing loss.…”
Section: Data Collection Proceduresmentioning
confidence: 90%
“…Osobe starijeg životnog doba smatraju se posebno vulnerabilnom grupom na koju izloženost buci nepovoljno utiče. U gerijatrijskoj populaciji buka prvenstveno utiče na gubitak sluha, što se češće uočava kod muškaraca (36). Takođe, sve je uočljiviji uticaj buke na kognitivni status osoba starijeg životnog doba, posebno usled hronične izloženosti buci, uz pojavu osećaja neprijatnosti i gubitak sluha.…”
Section: Uticaj Buke Na Osetljivu Populacijuunclassified